REPRESENTASI MILITERISTIK FIGUR PEREMPUAN DALAM KIDUNG AGUNG 6:10 : TAFSIR IKONOGRAFIS DALAM KONTEKS TIMUR DEKAT KUNO - Corina Tangdiombo; Sinta Sovia; Claudia (ADISAM PUBLISHER, 2026)
This study examines the militaristic representation of the female figure in Song of Songs 6:10 through an iconographic exegesis approach within the context of the ancient Near East. The central problem addressed is how the depiction “awesome as an army with banners” can be more deeply understood when situated within the visual-cultural matrix of ancient civilizations. The study employs a qualitative interpretive method combining linguistic-semantic analysis of the Hebrew text, comparative iconographic inquiry, historical-critical analysis, and intertextual reading. Primary data derives from the Hebrew text of Song of Songs 6:10, while secondary data is drawn from biblical, archaeological, and feminist theological literature. Results reveal that this militaristic imagery bears strong parallels to iconographic depictions of warrior goddesses from Mesopotamian, Canaanite, and Egyptian traditions, each simultaneously embodying beauty and cosmic power. This study concludes that the militaristic representation in Song of Songs 6:10 is not merely poetic ornamentation, but a theological statement positioning the female figure as a sovereign and dignified cosmic entity, while providing an iconographic foundation for gender-balanced interpretation of the Old Testament.